PENGARUH LATAR BELAKANG ANGGOTA DEWAN DAN PENGETAHUAN DEWAN TENTANG ANGGARAN TERHADAP PENGAWASAN KEUANGAN DAERAH (APBD) DENGAN PERSONAL BACKGROUND SEBAGAI PEMODERASI (Studi Empiris Pada DPRD Kabupaten Kuantan Singingi) - Riri Trycia Indra; Andreas Andreas; Alfiati Silfi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study aimed to texaminethe Effect of The Board Knowledge About The Budget Of The Regional Financial Supervision (APBD) with The Personal Background A Moderating Variable on all members of Parliament in the area Kuansing. Using survey data from 35 questionnaires distributed, which can be processed is 33 questionnaires. Multiple linear regression analysis is used with the help of software SPSS 20.0. The result indicate that there is an effect between the board knowledge about the budget with the Regional Financial Supervision (APBD) at statistic value 0,017. Personal background use has an effect of the relationship between knowledge about the budget and the Regional Financial Supervision (APBD) at statistic value 0,016. And accountability use has an effect the relationship between knowledge about the budget and the Regional Financial Supervision (APBD) at statistic value 0,030, but not with ransparency at statistic value 0,584.Keywords : The Regional Financial Supervision (APBD), Moderate variable, and Multiple linear regression.